Relações entre a adaptação a perturbações previsíveis e imprevisíveis e as funções executivas - Fabricia Quintao Loschiavo - Alvares (2010)
Acquisition of skilled behavior is an ongoing process that involves the transition from variable and inconsistent actions to consistent ones. In this way of thinking, It is relevant the role of stability and consistency in the development of skilled motor actions, which helps the ability to adapt to different environmental demands. One way of investigating adaptation is trying to understand the contribution of the central nervous system, as well as the different cortical circuits related to this process and their possible relationships with executive functions. Thus, the attentional deficit of hyperactive disorder was used in this study for experimental model of executive dysfunction. The aims was to investigate motor adaptation in the face of predictable and unpredictable perturbations and their relationship with executive functions, through a motor task (coincident timing task) and different instruments of neuropsychological assessment. The study included two groups (n=41), ADHDG (a group of individuals carrying the disorders) and CG (control group), whereas the same individuals were subjected to the same motor task and it was manipulated the predictability / unpredictability of perturbations. The experiment had two phases: pre-exposure, in which subjects performed the task in the sequence 2-3-4-5 with the time constrain of 3150ms; and exposure, with predictable and unpredictable perturbations with times of 2150ms and 4150ms, respectively, inserted between control trials. As performance measures it was used the absolute and constant errors and reaction time. The results were analyzed from the average offset of blocks of nine trials from each type of perturbation during exposition phase. First of all, it was realized the descriptive data analysis and, subsequently, the inferential analysis from the adopted measures in the study and at last, the performance measures were related with neuropsychological measures. It was used the non-parametric tests Friedman (intragroup comparison), Wilcoxon (post hoc), Mann-Whitney test (intergroup comparison) and the resampling statistical approach to correlated the motor measures with the neuropsychological measures Spearman and the level of significance adopted for all tests was p <0.05. The results of this study indicated that GTDAH, in general, showed lower performance when compared to CG for the three performance measures adopted in this study; the adaptation, considering the performance measures, was determined by the characteristics of the perturbations. It was correlations between executive functions: attention, reaction time and cognitive flexibility.